A critical analysis of the disconnection between science and practice in weight training - Cereda, Ferdinando (Physical Education and Sports: Studies and Research, 2025)
Background: Resistance training (RT) has emerged as a powerful tool for health promotion, with substantial scientific evidence supporting its beneficial effects across multiple physiological systems and psychological domains. Despite this robust knowledge base, a significant disconnection persists between scientific evidence and practical implementation in both clinical and everyday settings. Objectives: This study aims to critically examine this science-practice gap by analyzing common misconceptions surrounding RT and proposing strategies to enhance knowledge translation. Methods: Through a narrative review of scientific literature from PubMed, Scopus, and Google Scholar, the research synthesizes evidence regarding RT's scientifically validated benefits, prevalent myths, and effective communication approaches. Results: Findings show a concerning lack of scientific awareness among practitioners and end-users. Persistent misconceptions, such as "RT reduces flexibility" and "plant-based proteins are inferior for muscle hypertrophy," continue to circulate despite contradictory evidence. Conclusions: Improved scientific communication via targeted educational programs, digital platforms, and collaboration between researchers and policymakers is urgently needed to bridge this gap and maximize RT’s public health impact.